PENINGKATAN KUANTITAS DAN KUALITAS PERTANYAAN SEBAGAI INDIKATOR PROSES BERPIKIR PESERTA DIDIK MELALUI PENERAPAN DISCOVERY LEARNING DI KELAS XI MIA 7 SMA NEGERI 3 SURAKARTA TAHUN AJARAN 2014/2015 - Aziz, Subhan Abdul; Widoretno, Sri; Sari, Dewi Puspita (Universitas Sebelas Maret, 2015)
The objective of research was to improve the question’s quantity and quality as indicator of student’s thinking process through the application of discovery learning model at grade XI MIA 7 of State Senior High School 3 Surakarta academic year 2014/2015. This study was a Classroom Action Research (CAR), conducted in fourth cycles, consisting of four stages: planning, acting, observing, and reflecting. Subject were 32 students of XI MIA 7 State Senior High School 3 Surakarta academic year 2014/2015. Data collected through observation, interview, and documentation. The data validation used triangulation method. The obtained data were analyzed using qualitative-descriptive analysing technique that consist of data reduction, data display, and drawing conclusion. The result of research showed that application of discovery learning model improve the students question’s quantity and quality in grade XI MIA 7 State Senior High School 3 Surakarta acaedmic year 2014/2015. The improvement of students question’s quantity and quality was indicated by the student’s question at pre-cycle activity was 13 questions with C1 procedural question as the highest quality question become 126 questions with C4 metacognitive question as the highest quality question at the final cycle. The conclusion of research was the application of discovery learning model improve the quantity and quality of question as the indicator of student’s thinking process at grade XI MIA 7 State Senior High School 3 Surakarta academic year 2014/2015. Keywords: discovery learning, question’s quantity and quality